Kualitas diet dan kontrol glikemik pada orang dewasa dengan diabetes melitus tipe dua - Dodik Briawan; Mahfuzhoh Fadillah Heryanda; Sudikno Sudikno (Jurnal Gizi Klinik Indonesia, 2021)
Diet quality and glycemic control in adults with type two diabetes mellitusBackground: As assessed by Alternate Healthy Eating Index (AHEI), diet quality is correlated with glycemic control through its effect on glucose-insulin homeostasis. Studies are evaluating the diet quality index in Indonesia, especially its relation to glycemic control in those with type 2 diabetes mellitus (T2DM), are lacking. Objective: To analyze the association between diet quality and glycemic control T2DM in adults. Methods: This research was a cross-sectional study using data from "Cohort study of non-communicable disease risk factors" in 2016 by the Indonesia Ministry of Health. Hundred and five (105) subjects diagnosed with T2DM, aged 25-65, were recruited in this study. A 24-hour dietary recall was collected, and a diet quality index referred to the USA adapted AHEI-2010 was assessed. The portion of food components was modified based on the Indonesian Dietary Guidelines. Glycemic control was evaluated according to fasting blood glucose (FBG) and 2-hours-post-75-g glucose load (2h-PG). Spearman correlation test was applied in this analysis. Results: A mean age of subjects was 51 years, and 77.1% out of 105 subjects were women. Mean value of FBG 123.5 and 2h-PG 228.9 mg/dL. The total score of AHEI was 53.8. There was not a significant correlation between the total score of AHEI with FBG (r= -0.079) and 2h-PG (r= -0.069) (p>0.05). However, there was a significant association between the fruits score and 2h-PG (r= -0.224) (p<0.05). Most of the subjects consumed fruits containing low-moderate fructose, such as bananas, oranges, papayas. Conclusions: In T2DM, there was no significant association between the total score of current diet quality and poor glycemic control, except for the fruits component.